Governance and Africa's financial development amid sustainable digitalisation - Ejemeyovwi, Jeremiah O; Osabuohien, Evans S; Bowale, Ebenezer I K (University of the Witwatersrand, Johannesburg, 2023)
The technological revolution presents opportunities for financial development in Africa. However, the opportunities need to be supplemented with good governance to ensure efficiency and optimal welfare gains. It is therefore worth investigating whether governance, as well as digitalisation shocks, are crucial for the relatively underdeveloped nature of the financial system of such countries and regions. This study therefore examines the impact of governance and digitalisation shocks on financial development in Africa. Specifically, the study tests out the triple-helix model on five uniquely selected African regional representative countries, namely Botswana, Democratic Republic of Congo (DRC), Nigeria, Rwanda and Tunisia for robust and comparative policy estimates. Notably, the study utilised data from the World Development Indicators of the World Bank Group (2023). It adopts the Bayesian Vector Auto-Regressive (VAR) empirical modelling to achieve this objective. The technique was utilised after the model stability test was carried out, using the auto-regressive roots test. The impulse response function across Africa is inferred from the model simulation. The study's findings and recommendations contribute to the literature and economic agents (such as multinationals), empirical evidence of the theoretical reflections of digitalisation and governance on financial development in Africa.
Keywords: African Governance; Digital Age; Financial development; Digitalisation; Sustainable digitalisation; SDG-9: Industry, innovation and infrastructure